Utilization Of Mixed Agroindustrial By - Products For Alkaline Lipase Production From Penicillim chrysogenum - Rajeswari, T (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTThe aim of this work was to produce lipases by solid-state fermentation (SSF) using agroindustrial residues as substrate. For a group of fourty fungal strains received from Karpagam Microbial Culture Collection Center (KMCCC) were screened for exogenous lipolytic activity. Among the evaluated strains, the Penicillim chrysogenum was selected by presenting the best enzymatic production. Optimization of fermentation conditions such as substrate, temperature, pH, and moisture content and incubation period for maximum lipase production was examined under solid state fermentation. A comparative study on the production of extra cellular lipase by solid-state fermentation using Penicillim chrysogenum with various substrates has been made. Wheat bran showed the highest enzyme activity of 460 units per gram of dry fermented substrates (U/ gds), but with the combination of wheat bran and black gram husk (1: 1) resulted in a higher enzyme yield of 650 U/ gds after 7 days of incubation with 40 % of initial moisture content of the substrate at pH 9.